Efektivitas Ketentuan Insentif dan Disinsentif Terkait Perizinan Pemanfaatan Ruang Pada Zona Perdagangan dan Jasa Berdasarkan Perda Nomor 5 Tahun 2012 Tentang Rencana Tata Ruang Wilayah Kota Sungai Penuh Tahun 2011 – 2031 - Harifinal, Harifinal; Azed, Abdul Bari; Supeno, Supeno (Universitas Batanghari Jambi, 2024)
Even though the Regional Regulation on the Regional RTRW of Sungai Banyak City has been stipulated, the use of existing space is not yet in accordance with the plans that have been determined. This is indicated by the fact that the building does not meet the building construction requirements for both KDB, GSB and KDH. Provisions on Incentives and Disincentives Related to Licensing for Space Utilization in Trade and Service Zones based on the Regional Regulation on the RTRW of Sungai Banyak City have not been implemented effectively, this can be seen from the 182 Building Approvals that have been issued by the Sungai Full City Government from 2021 to 2023, they are not implemented provisions for incentives and disincentives for controlling space utilization. Factors that become obstacles include the fact that the Regional Regulation has not yet been established, there is still a lack of Satpol PP members, the facilities and infrastructure are still not complete, the community's legal awareness is still low, and people are building houses using the process of adjunct direction from traditional institutions. The efforts made by the Regional Government of Sungai Banyak City to overcome these obstacles include drafting the Draft Regional Regulation on the RTRW Revision, proposing additional members of the Civil Service Police Unit, maximizing honorary personnel, procuring facilities and infrastructure, socializing the Regional Regulation on Spatial Planning to the community, collaborating with traditional institutions in the planning process , utilization and control of the spatial planning of Sungai Banyak City.